1991
DOI: 10.1007/bf02662283
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of the esterification reaction between castor oil and oleic acid

Abstract: In this study, esterification of castor oil with oleic acid was investigated in view of the reaction kinetics under various conditions. Potassium hydroxide, p-toluenesulfonic acid and tin chloride (SnCI22H20) were used as catalysts. Reaction was carried out at 200~ 225~ and 250~ by using equivalent proportions of the reactants. For tin chloride, experimental data fitted the second-order rate equation, while for the other catalysts the obtained data fitted the third-order rate equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…We assumed, like other authors [19,24], that the reaction is irreversible under the applied conditions e.g. in the absence of water, which was removed by continuous distillation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed, like other authors [19,24], that the reaction is irreversible under the applied conditions e.g. in the absence of water, which was removed by continuous distillation.…”
Section: Resultsmentioning
confidence: 99%
“…It was found [20][21][22][23][24], that the reaction kinetics is of second order. This was proved by Hartmann [13] for uncatalyzed esterification reaction, but only for equivalent weight concentration of the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the estolides were not characterized or their physical properties determined. Erciyes et al, (1991) However, Erdem's work did provide insight into the reaction mechanism. Later work on the kinetics of the esterification reaction of castor with lauric acid in the presence of various Lewis acid catalysts by Kulkarni et al, (2003) demonstrated that n-butyl titanate was an effective catalyst for the formation of estolide.…”
Section: Synthetic Glyceride Estolidesmentioning
confidence: 99%
“…At a molar ratio of methanol to soybean oil of 6 1 , a second-order mechanism with a fourth-order shunt mechanism best described the kinetics. Other kinetic studies include transesterification of CL8 unsaturated fatty acids contained in tall oil with methanol ( l l ) , acidolysis of castor oil with oleic acid (12). esterification of oleic acid with l-octanol using an immobilized enzyme on polymeric support (13), and the idealized kinetic model for the lipase-catalyzed interesterification of fats and oils (14).…”
mentioning
confidence: 99%